Creating Customer Value in a Digitally Transformed Future. (November 2015) - Connor, Michael
Abstract: Today's market is being driven by continually accelerating innovation. Much of that innovation is being driven by the Internet, which has become a global platform for innovation and engagement. Through it we can connect people, processes, data, systems and devices faster, more effectively and more powerfully and innovate faster because of it than at any time in history. That capability and the innovation it enables are rapidly changing what customers value and are blurring the boundaries between how we create products and services as well as companies, and how we engage customers. Those changes are leading us into a market composed of digital ecosystems and intelligent products that anticipate and facilitate high-value customer/user outcomes based on the users context. To compete in the digitally transformed future will require not just understanding the technology, but also being immersed in the cultures creating it, and working collaboratively with customers and other participants in the digital ecosystems to identify and create new breakthrough value. For products and services to be competitive they must be highly personalized for users and contextualized based on their location and needs at the moment. Transforming your company into an organization that can compete and lead in that future is critical to your success. It requires a top-down commitment from your most senior executives. And it requires working collaboratively with your most visionary customers and partners to create a digital vision and a continually adaptive strategy and transformation plan. This article provides a series of questions and recommended action items to help you develop that vision and strategy and to help you become a vibrant part of that digital future.